The Effect of the Use of Augmented Reality (AR) Media on the Mathematical Problem-Solving Ability of Grade IV Elementary School Students - Widiastuty, Ade Evy; Yamtinah, Sri; Sukarno, Sukarno (Universitas Sebelas Maret, 2026)
The low mathematical problem-solving ability of fourth-grade elementary school students is an educational challenge that requires innovative learning media solutions. This study aims to determine the effect of using Augmented Reality (AR) media on the mathematical problem-solving ability of fourth-grade elementary school students. The research method used was a quasi-experiment with a nonequivalent control group design, involving two classes selected through purposive sampling. Data were collected using test instruments in the form of essay questions that had been tested for validity and reliability. The data analysis technique included prerequisite tests (normality and homogeneity), independent samples t-test for hypothesis testing, and N-Gain analysis to measure the effectiveness of the treatment. The results showed that the class that used AR media obtained a higher average post-test score than the control class that used conventional media. Statistical analysis using an independent samples t-test showed a significant difference between the two groups. Furthermore, observational data on student activities showed an increase in engagement and interaction with mathematical concepts during learning. In conclusion, the use of Augmented Reality (AR) media had a positive and significant effect on improving the mathematical problem-solving skills of fourth-grade elementary school students.